Sebuah Apakah PjBL yang Terintegrasi dengan Media Pembelajaran Efektif Meningkatkan Kreativitas Siswa pada Topik Biologi?: Tinjauan Pustaka Sistematis dan Analisis Bibliometrik - Richa Amalia; Afreni Hamidah; Jodion Siburian (Postgraduate, University of Mataram, 2025)
Research on integrated PjBL in learning media has grown rapidly in recent years, attracting increasing attention from academics and practitioners. However, the literature examining the impact of integrated PjBL on learning and enhancing student creativity is currently sparse and lacks a comprehensive view of how such integration works in education. To bridge this gap, our review comprehensively examined 16 academic articles sourced from the Google Schoolar database, synthesizing previous research on the integration of PjBL in learning media, specifically in biology topics. Using a systematic literature review and incorporating bibliometric analysis, our study provides an analysis of the current management research landscape on how PjBL integrated into learning media can enhance student creativity in biology topics. Our study shows that the integration of PjBL with learning media, particularly interactive digital media, is significantly positively correlated with increased student creativity, manifested through originality, elaboration, and idea fluency. Based on our literature review, we establish a future research agenda and provide practical implications.